TRANSFORMASI PENGAJARAN DI SEKOLAH: PELATIHAN METODE BELAJAR AKTIF UNTUK GURU DALAM MENINGKATKAN KETERLIBATAN DAN MOTIVASI BELAJAR SISWA DI SMPTK DAN SMTK PRESBITERI BALI - C. Mathilda V. Bolang; Helsa Helsa; Sylvia Kurniawan; Alfredo Alfredo; Sri Lanawati (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
Student engagement and learning motivation play a crucial role in enhancing the quality of education while preventing low academic achievement and the risk of dropout. Within the context of Generation Z, who were born in the digital era, students possess unique characteristics as visual learners with shorter attention spans, a preference for interactive learning, and a strong need for meaningful learning experiences. These conditions require teachers to adopt more relevant instructional strategies, one of which is active learning, which has been shown to enhance student motivation and engagement. This community service program was implemented at SMPTK and SMTK Presbiteri Bali, involving 11 teachers in three training sessions: (1) understanding the characteristics of Generation Z students, (2) a workshop on the application of active learning, and (3) a reflective post-implementation discussion. Descriptive analysis indicated an increase in the average scores of student engagement and motivation, rising from 208.3 to 215.9 after the program. However, the paired samples t-test revealed that the difference in scores before and after the program was not statistically significant, t(8) = -1.509, p = 0.170 (p > 0.05). Nevertheless, qualitative evaluations revealed that teachers felt supported, more confident, and motivated to enrich their instructional strategies. These findings highlight the importance of practice- and case-based teacher training conducted continuously to strengthen the implementation of active learning in addressing the educational needs of Generation Z.